Characterization of dynamic changes in cardiac microstructure after reperfused ST-elevation myocardial infarction by biphasic diffusion tensor cardiovascular magnetic resonance - Rajakulasingam,R; Ferreira,P; Scott,A; Khalique,Z; Azzu,A; Molto,M; Conway,M; Falaschetti,E; Cheng,K; Hammersley,D; Cantor,E; Tindale,A; et al. (European Heart Journal, 2025)
Background and Aims: Microstructural disturbances underlie dysfunctional contraction and adverse left ventricular (LV) remodelling after ST-elevation myocardial infarction (STEMI). Biphasic diffusion tensor cardiovascular magnetic resonance (DT-CMR) quantifies dynamic reorientation of sheetlets (E2A) from diastole to systole during myocardial thickening, and markers of tissue integrity (mean diffusivity [MD] and fractional anisotropy [FA]). This study investigated whether microstructural alterations identified by biphasic DT-CMR: (i) enable contrast-free detection of acute myocardial infarction (MI); (ii) associate with severity of myocardial injury and contractile dysfunction; and (iii) predict adverse LV remodelling. Methods: Biphasic DT-CMR was acquired 4 days (n=70) and 4 months (n=66) after reperfused STEMI and in healthy volunteers (HVOLs) (n=22). Adverse LV remodelling was defined as an increase in LV end-diastolic volume ≥20% at 4 months. MD and FA maps were compared with late gadolinium enhancement images. Results: Widespread microstructural disturbances were detected post-STEMI. In the acute MI zone, diastolic E2A was raised and systolic E2A reduced, resulting in reduced E2A mobility (all p<0.001 vs adjacent and remote zones and HVOLs). Acute global E2A mobility was the only independent predictor of adverse LV remodelling (odds ratio 0.77; 95% confidence interval 0.63–0.94; p=0.010). MD and FA maps had excellent sensitivity and specificity (all >90%) and inter-observer agreement for detecting MI presence and location.Conclusions: Biphasic DT-CMR identifies microstructural alterations in both diastole and systole after STEMI, enabling detection of MI presence and location as well as predicting adverse LV remodelling. DT-CMR has potential to provide a single contrast-free modality for MI detection and prognostication of patients after acute STEMI.